(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
Increasingly advanced equipment may now be smaller and use less power thanks to technological advancements. These deteriorate but also power ushers in new wearable technology paradigms, with a slew of embedded systems cooperating or at the very least having better communication capabilities. Smart watches and remote monitoring are examples among those new paradigms. These devices are generally powered by batteries. However, batteries have a number of drawbacks, including the need to renew or refresh them on a regular basis, as well as their considerable size and weight when compared to current technological products. Collecting (harvesting) energies first from ambient to either recharge a battery or directly charge the digital circuit is one way to get over this power limits. This article presents numerous approaches to design a space is provided network and data on the sort of energies available.